2015
DOI: 10.4103/1319-2442.160224
|View full text |Cite
|
Sign up to set email alerts
|

Causes of chronic kidney disease in Egyptian children

Abstract: There are very few published reports on the causes of chronic kidney disease (CKD) in Egyptian children. We reviewed the records of 1018 (males 56.7%, age ranged from 1 to 19 years) Egyptian patients suffering from CKD and followed-up at the pediatric nephrology units (outpatient clinics and dialysis units) of 11 universities over a period of two years. The mean of the estimated glomerular filtration rate was 12.5 mL/min/1.73 m 2 . Children with CKD stage I and stage II comprised 4.4% of the studied group, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…Children with CKD face a lifelong increase in morbidity and mortality, as well as a poor QOL 1 . In the absence of a national registry, the exact incidence of CKD in children in Egypt is not known; however, a relatively recent study from 11 university hospitals reported 1018 Egyptian children suffering from various stages of CKD, signifying the burden of this illness 2 …”
Section: Introductionmentioning
confidence: 99%
“…Children with CKD face a lifelong increase in morbidity and mortality, as well as a poor QOL 1 . In the absence of a national registry, the exact incidence of CKD in children in Egypt is not known; however, a relatively recent study from 11 university hospitals reported 1018 Egyptian children suffering from various stages of CKD, signifying the burden of this illness 2 …”
Section: Introductionmentioning
confidence: 99%
“…In a similar study conducted in Tehran, 86% [19] of the patients required transplantation and mainly had hemodialysis. In a study done in Egypt, 93.5% [20] of patients with ESRD were undergoing hemodialysis. In another research conducted in China, 15.8% of patients needed alternative treatment, of which 66.5% were under dialysis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted by Safouh H., et al (19) and Staples A.O., et al (20) revealed that the most common diagnosis was obstructive uropathy. In addition, Olowu W.A., et al (21) revealed in a study conducted in Nigeria that the most common etiology of CKD among the studied population was glomerular disease and in a study conducted by Cerón A., et al (22) , the most frequent presentation was chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%